Exploring food waste prevention through advent food consumption: The role of perceived concern, consumer value, and impulse buying - Liao, Chuanhui; Qiao, Liguang; Wang, Xuanzheng; Lu, Shanshan (Frontiers in Sustainable Food Systems, 2022)
Every year, about one-third of food intended for human consumption is wasted along the distribution chain, in which advent food contributes a significant portion. Advent food marketing and consumption are suggested as the primary channel to use advent food and reduce food waste. With the booming of the advent food market, it is necessary to explore factors attributed to advent food purchase and food waste reduction behaviors. This study explored what consumer concern and value might influence food waste reduction intention in the context of advent food consumption. Based on a survey of Chinese consumers (N = 509), this study develops a structural equation and tests the hypotheses with consistent Smart-pls software. Results show that, as expected, health concerns, utilitarian value, and impulse buying significantly affect food waste reduction intention. Price concern, utilitarian value, and hedonic value exert direct positive effects on impulse buying, which negatively influence food waste reduction intention. In the mediating effect analysis, impulse buying partially mediates the relationship between price concern and food waste reduction intention. Theoretical and managerial implications and recommendations for future research are discussed.